Farmers' manual on small-scale tilapia cage farming in Ghana - Agyakwah, Seth K.; Asmah, Ruby; Mensah, Emmanuel Tetteh-Doku; Ragasa, Catherine; Amewu, Sena; Tran, Nhuong; Oyih, Mathew; Ziddah, Peter (Water Research Institute, 2020)
This manual provides a comprehensive step-by-step guide to cage aquaculture. It includes tips on site selection, site preparation, cage design and construction, farming practices (cage preparation, stocking, feeding), biosecurity and fish health management, harvesting and marketing and recordkeeping – all of which are critical elements of a successful tilapia cage farming business operation.